Geographical patterns of intraspecific genetic diversity reflect the adaptive potential of the coral Pocillopora damicornis species complex - M. Carr; C. Kratochwill; T. Daly-Engel; T. Crombie; R. van Woesik (PLoS ONE, 2025)
Marine heatwaves are increasing in intensity and frequency however, responses and survival of reef corals vary geographically. Geographical differences in thermal tolerance may be in part a consequence of intraspecific diversity, where high-diversity localities are more likely to support heat-tolerant alleles that promote survival through thermal stress. Here, we assessed geographical patterns of intraspecific genetic diversity in the ubiquitous coral Pocillopora damicornis species complex using 428 sequences of the Internal Transcribed Spacer 2 (ITS2) region across 44 sites in the Pacific and Indian Oceans. We focused on detecting genetic diversity hotspots, wherein some individuals are likely to possess gene variants that tolerate marine heatwaves. A deep-learning, multi-layer neural-network model showed that geographical location played a major role in intraspecific diversity, with mean sea-surface temperature and oceanic regions being the most influential predictor variables differentiating diversity. The highest estimate of intraspecific variation was recorded in French Polynesia and Southeast Asia. The corals on these reefs are more likely than corals elsewhere to harbor alleles with adaptive potential to survive climate change, so managers should prioritize high-diversity regions when forming conservation goals.